Reading Magical Realism in Salman Rushdie’s Midnight’s Children for Supporting EFL Students’ Cross-Cultural Awareness - Galuh Dwi Ajeng; Aksendro Maximilian (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2023)
The present study explores the magical realism contents in the Midnight’s Children by Salman Rushdie. It also aims to investigate the way the magical realism contents to be adapted and integrated into the cross-cultural understanding material to support the EFL students’ cross-cultural awareness. The qualitative research method is employed for analysing the primary source by consulting it to the secondary sources. From the story, it is found that the struggle is available between two opposing structures in a mystical realist document, and one of them is working toward the development of a fantasy universe from the other. These are the worlds of fantasy and life, and they are all present and vying for the reader's interest. Thus, the study may deduce that Rushdie employs magical realist features such as time dilation and the introduction of myth, legends, and folklore. Rushdie has built something unique with Midnight’s Children, and Saleem is honestly attempting to tell the tale of his existence, and the life of the new country. Moreover, based on the contents found, the instructional activities can be designed by adapting the magic realism content found in the story to build the cross-cultural awareness of the Indonesian EFL students. Moreover, magic realism content can also be an alternative and variation on the language and cultural classes.